2016
DOI: 10.1021/acs.molpharmaceut.5b00987
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophage-Mediated Targeted Therapy of Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive form of breast cancer. TNBC is often infiltrated with a large number of macrophages, which in turn promote tumor growth and metastasis. In this study, tumor-associated macrophages (TAMs) were exploited as a target to deliver doxorubicin (DOX), a chemotherapeutic agent, to TNBC using nanoparticles surface-functionalized by i) acid-sensitive sheddable PEGylation and ii) modifying with mannose (i.e. DOX-AS-M-PLGA-NPs). In mice with orthotopic M-Wnt tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…Recently, the same group applied the combination of mannose modification and acid-sensitive sheddable PEGylation to deliver doxorubicin to TAMs in triple-negative breast cancer. They reported that a single intravenous injection of such functionalized nanoparticles significantly reduced macrophage population in tumors within 2 days, and the repeated injections kept the macrophage population at a lower level for 9 days [132]. …”
Section: Nanomedicines Targeting Dysfunctional Macrophage-associatmentioning
confidence: 99%
“…Recently, the same group applied the combination of mannose modification and acid-sensitive sheddable PEGylation to deliver doxorubicin to TAMs in triple-negative breast cancer. They reported that a single intravenous injection of such functionalized nanoparticles significantly reduced macrophage population in tumors within 2 days, and the repeated injections kept the macrophage population at a lower level for 9 days [132]. …”
Section: Nanomedicines Targeting Dysfunctional Macrophage-associatmentioning
confidence: 99%
“…Such tumor contains a high population of tumor-associated macrophages (TAMs). 28 M-Wnt cells were cultured in RPMI 1640 containing 10% FBS and 1% P/S. All cell culture media and reagents were from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…As TNBC is often infiltrated with high numbers of TAMs, Niu et al showed that doxorubicin-containing nanoparticles targeting TAMs via mannose-mannose receptor recognition reduced TAM density and inhibited tumor growth in an orthotopic mouse model of TNBC. In addition, the effectiveness of these nanoparticles is found to be dependent on their ability to target TAMs within TNBC stroma [96]. Other novel approaches to target TAMs in vivo include the use of DNA vaccines against TAM-derived protein legumain in several murine cancer models [97] as well as the success of using clodronate/liposome to delete TAMs as an adjuvant therapy to boost antitumor immunity induced by a TLR agonist-conjugated peptide Pam2IDG [98].…”
Section: Toll-like Receptor Agonistsmentioning
confidence: 99%